Computational study on a cobalt-based complex compound with amine ligand in X-doped (X = Co, Ru, Rh) Ca12Al14O33 functional material as an innovative catalyst by NaBH4 hydrolysis for determining hydrogen generation process - Celik, Fatih Ahmet; Karabulut, Ezman; Izgi, Mehmet Sait; Yilmaz, Mucahit; Onat, Erhan (Pergamon-Elsevier Science Ltd, 2024)
Sodium borohydride (NaBH4) has been generally studied as a source of hydrogen (H2) due to its important advantages with the development of support materials and catalysts for H2 release in the energy sector. In this context, we carry out molecular dynamics (MD) simulations by using extended tight-binding (xTB) model Hamiltonian based on density functional theory (DFT) and analyze the Ca12Al14O33 functional material doped X metals (X = Co, Ru, Rh) as a catalyst with [Co(III)(N3)3(C9H8N2)2] as complex compound with amine ligand from NaBH4 hydrolysis for H2 production. The use of a functional material doped by X metals causes to the high rate in H2 production when compared to without functional material doped by X metals. The increase of complex compound with amine ligand facilitates H2 production. Rh on the functional material displays the best catalytic performance compared to Ru and Co to increase the H2 production rate. Also, the increment of temperature has a positive effect on the H2 production rate with functional material doped Co, Ru and Rh metals. Thus, Ca12Al14O33 support material doped with noble metals appears promising as an innovative catalyst for H2 production.
Keywords: Hydrogen generation; Hydrolysis; Sodium borohydride; Functional material doped noble metals; Complex compound with amine ligand